Effect of torsion on externally prestressed segmental concrete bridge with shear key - Al-Gorafi, Mohammed Abdulla Ismail; Abang Ali, Abang Abdullah; Jaafar, Mohd Saleh; Othman, Ismail; Anwar, Mohammed Parvez; Muhammad Rashid, Raizal Saifulnaz (Science Publications, 2009)
Externally Prestressed Segmental (EPS) concrete box sections are widely used in the construction of bridge structures today. EPS concept has become an attractive tool for rehabilitation and strengthening of existing bridges which have insufficient strength and/or excessive deflection and cracking. Problem statement: EPS bridges are affected by combined stresses (bending, shear, normal, and torsional) at the joint interface between the segments. However, very limited researchers studied this type of bridges under combined stresses. Approach: This paper presented an experimental investigation of the structural behaviour of EPS bridge with shear key under torsion. Four beams were tested, each containing three segments that were presetressed using two external tendons. A parametric study of two different external tendon layouts as well as different levels of torsional force applied by different load eccentricities was conducted. Results: The effect of torsion was evaluated in terms of vertical deflections, concrete and tendon strains, failure loads and failure mechanisms. It was concluded that torsion has a significant effect in the structural behaviour of external prestressed segmental box girder beams. Torsion not only alters failure load of the beam but also changes the type of failure mechanism. It was also investigated that harp tendon layout results in better structural behaviour in term of deflection and tendon strain as compared with the straight tendon. Recommendations: It recommended including the effect of joint (flat and shear key) type as well as the effect of tendon layout under torsion to obtain comprehensive behavior of EPS bridge.